Terapi Kelompok Suportif untuk Meningkatkan Harga Diri pada Narapidana Menjelang Persiapan Pulang - Hana Hana (University of Muhammadiyah Malang, 2021)
Subjects in this study were convicts who are in the process of preparing to go home. Assessment is used by using interviews, observations and providing a Self Esteem Inventory Scale. The intervention given to the subject was to provide therapy to supportive groups consisting of eight sessions. The aim of this intervention is to increase selfesteem in convict. The results of the intervention showed good changes where before taking therapy the results of the self-esteem scale of the five subjects were at a low level but after attending therapy the results of the subject scale increased. Two subjects rose to moderate levels and three subjects rose to high levels.